Hot Weather Angels associated with High Level Temperature Inversions - KULSHRESTHA, S. M. (MAUSAM, 1962)
During the hot weather months (April to June), the CPS-9 radar installed at Safdarjung Airport, New Delhi, has been recording angel echoes having certain peculiar characteristics; the most important amongst them being the apparent association of the angel activity with an upper level temperature inversion or an isothermal layer between 6 to 11 km above ground. Examples of this type of angel activity, observed on seven different dates spread over a three-year period (1958 to 1960) are presented and their characteristics discussed in this paper. Their apparent association with high level temperature inversion is also explained.